Pseudomonas syringae pv. syringae B728a Regulates Multiple Stages of Plant Colonization via the Bacteriophytochrome BphP1 - McGrane, Regina (mBio, 2017)
Light may be an important environmental signal for plant-associated bacteria, particularly those that live on leaves. An integrated network of red/far-red- and blue-light-responsive photosensory proteins is known to inhibit swarming motility in the foliar plant pathogen Pseudomonas syringae pv. syringae B728a. Here we elucidated factors in the red/far-red-light-sensing bacteriophytochrome BphP1 signal transduction pathway and report evidence for a role of BphP1 in multiple stages of the P. syringae B728a life cycle. We report that BphP1 signaling involves the downstream regulator Bsi (bacteriophytochrome-regulated swarming inhibitor) and an acyl-homoserine lactone (AHL) signal. Loss of bphP1 or bsi resulted in the early initiation of swarm tendrils during swarming motility, a phenotype that was dependent on red/far-red light and reversed by exogenous AHL, illustrating that the BphP1-Bsi-AHL pathway inhibits the transition from a sessile state to a motile state. Loss of bphP1 or bsi resulted in larger water-soaked lesions induced on bean (Phaseolus vulgaris) pods and enhanced movement from soil and buried plant tissues to seeds, demonstrating that BphP1 and Bsi negatively regulate virulence and bacterial movement through soil to seeds. Moreover, BphP1, but not Bsi, contributed to leaf colonization; loss of bphP1 reduced survival on leaves immediately following inoculation but enhanced the size of the subsequently established populations. Neither Bsi nor Smp, a swarm motility-promoting regulator identified here, affected leaf colonization, indicating that BphP1-mediated contributions to leaf colonization are, at least in part, independent of swarming motility. These results demonstrate that P. syringae B728a red-light sensing involves a multicomponent, branched regulatory pathway that affects several stages of its life cycle.